Effect of long-term fertilization of nitrogen, phosphorus and organic fertilizer on PLFA in Chinese arable mollisol - BAI Zhen; ZHANG Ming; YAN Ying; ZHENG Li-chen; ZHANG Xu-dong (浙江大学学报. 农业与生命科学版, 2008)
Surface soil samples of 8 different fertilization treatments, including CK, N, P, NP, MCK, MN, MP, MNP in Gongzhuling national long-term experimental site, were taken on May 31, 2006. PLFA and the contents of organic carbon, total nitrogen, alkali-hydrolysable nitrogen (AN), available phosphorus (AP), readily available potassium (RAK), NO3--N and NH4+-N as well as soil pH of each sample were measured. The results show that organic fertilizer amendments (MCK, MN, MP and MNP) and application of single P significantly promoted soil microbial growth and increased the fungi-to-bacteria ratio. Long-term application of single N did not affect bacterial or fungal growth. In comparison with MCK, the combined application of chemical and organic fertilizers had different effects on fungi and bacteria: as for total bacterial PLFA, the order was MCK (54.7 nmol·g-1) >MP (49.7 nmol·g-1) > MN (44.8 nmol·g-1) > MNP (42.6 nmol·g-1); however, fungi were significantly promoted by the addition of chemical fertilizers with the order of MP (28.5 nmol·g-1) > MN (26.0 nmol·g-1) >MNP (22.8 nmol. g-1) >MCK (22.0 nmol·g-1). Multivariate regression analysis suggested that total microbial and bacterial biomass were significantly affected by readily available potassium and NO3--N, and fungal biomass was influenced by available phosphorus and NH4+-N. NO3--N and total nitrogen were the most important factors affecting the growth of G+, while the most important factor for G- was readily available potassium.